Prediction of Turkey's Denim Trousers Export Using Artificial Neural Networks and the Autoregressive Integrated Moving Average Model - (:unkn) unknown (INST CHEMICAL FIBRES, 2011)
In this study, Turkey's denim trouser export was predicted using ANN and ARIMA models. ANN models were composed from the import of denim trousers, the minimum wage, the price of cotton, electricity, and water, the value of TRY against USD, the credit usage of ready-made clothing enterprises, export credits, the real effective exchange rate, brands of denim trousers, and the denim trouser Balasa Index. It is observed that the best prediction is provided by MLP, the second - with ERNN and the third - with ARIMA. The reason why the export of denim trousers is not completely modeled can be explained by the economic downturn, which began in 2008 and still continues. However, it is clearly seen that ANN models predict more successfully than ARIMA ones.
Keywords: Artificial Neural Networks; ARIMA; prediction; export; denim pants